Resistance to legume pod borer (Maruca vitrata Fabricius) in cowpea: genetic advances, challenges, and future prospects - Ayenan, M.A.T.; Sodedji, F.A.K.; Agbahoungba, S.; Nguetta, S.P.A.; Agoyi, E.E.; Sossou, S.H.; Mamadou, C.; Assogbadjo, A.E.; Kone, D. (Journal of Crop Improvement, 2019)
Cowpea (Vigna unguiculata (L.) Walp) is a highly nutritious grain legume crop in the world. However, cowpea production is constrained by legume pod borer (Maruca vitrata Fabricius) (LPB), which feeds on various parts of cowpea plant, causing a complete crop failure. An analysis of the existing literature revealed LPB as a serious threat to cowpea production worldwide, with a more noticeable damage in Africa. Attempts to develop and use LPBresistant cowpea varieties have not shown significant results because of challenges, such as interspecific crossing barriers, genetic variability among LPB strains, effects of genotype-byenvironment interaction, limited knowledge of the genetic architecture of the trait, and the socio-political barriers to the adoption of transgenic cowpea varieties in some countries. Combining multi-environment trials with precise phenotyping would help optimize selection of best-performing cowpea genotypes to reduce LPB infestation. Many molecular tools (e.g., markers systems, genetics maps, high-throughput genotyping, and quantitative trait loci (QTL) analysis) are available to support breeding for LPB resistance in cowpea. In addition, mutation breeding, tissue culture, reverse genetics, clustered regularly interspaced short palindromic repeats (CRISPR) technologies can be used to increase genetic variability in cowpea for LPB resistance. The effective use of these technologies relies on an enabling legal and socio-economic-political environment for fast development and adoption of LPB-resistant cowpea varieties.
Research Article
Keywords: genomic resources; Genetic architecture; insect pest; pod borer; Vigna unguiculata